2012
DOI: 10.1021/pr300565w
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Carbonic Anhydrase IX Interactome Reveals Proteins Assisting Its Nuclear Localization in Hypoxic Cells

Abstract: Carbonic anhydrase IX (CA IX) is a transmembrane protein affecting pH regulation, cell migration/invasion, and survival in hypoxic tumors. Although the pathways related to CA IX have begun to emerge, molecular partners mediating its functions remain largely unknown. Here we characterize the CA IX interactome in hypoxic HEK-293 cells. Most of the identified CA IX-binding partners contain the HEAT/ARM repeat domain and belong to the nuclear transport machinery. We show that the interaction with two of these prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 54 publications
3
73
0
Order By: Relevance
“…Utilization of monoclonal antibodies, such as M75 and G250, to recognize the proteoglycan-like (PG) domain (the N-terminal extension unique to this isoform) of CA IX have shown effectiveness in disrupting the ability of the enzymes function in regulating tumor cell adhesion and motility [139, 140]. More recently, the monoclonal antibody 6A10 has been developed to mediate CA XII activity also acting as a potential anticancer therapeutic [124, 125].…”
Section: Resultsmentioning
confidence: 99%
“…Utilization of monoclonal antibodies, such as M75 and G250, to recognize the proteoglycan-like (PG) domain (the N-terminal extension unique to this isoform) of CA IX have shown effectiveness in disrupting the ability of the enzymes function in regulating tumor cell adhesion and motility [139, 140]. More recently, the monoclonal antibody 6A10 has been developed to mediate CA XII activity also acting as a potential anticancer therapeutic [124, 125].…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative protein expression profiling revealed that overexpression of YWHAE prompt the proliferation of renal cancer cells [32]. CAND1 may also promote the progression of renal cell carcinoma through its interaction with carbonic anhydrase IX [33]. Whether the up regulation contributes to the pathogenesis of renal failure needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly enough, a recent proteomic study searching for the interacting partners of CA IX revealed a group of intracellular proteins that belong to nuclear transport machinery, including XPO1 exportin and TNPO1 importin (Buanne et al, 2013). Although the interaction occurs via the C-terminal region of CA IX, it involves entire (mature) CA IX molecule that can be detected in the nuclear and perinuclear regions of hypoxic cells through the catalytic domain-specific antibody.…”
Section: Fig 2 Schematic Illustration Of the Transport Routes Of Thementioning
confidence: 99%